THE EFFECT OF THE PRICE SETTING OF RICE BY BULOG BANDA ACEH ON THE RICE MARKET MECHANISM IN THE CONCEPT OF TAS'IR AL-JABARI - Alif, Muhammad; Iqbal, Muhammad (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2024)
Price, as a determinant of the value of a good or service, reflects the interaction between supply and demand. Changes in commodity prices significantly impact business actors, making market equilibrium crucial to maintain. The level of competition in the market also affects market conditions. From a fiqhiyah perspective, the government can restructure the market through tas’ir al-jabari, which involves price setting based on various market studies and evaluations. This study aims to assess the appropriateness of the theory and concept of tas’ir al-jabari in the price setting of rice by Bulog in Banda Aceh. This research employs a juridical-sociological approach with descriptive-analytical research methods to clarify the research object, focusing on the impact of Bulog Banda Aceh's rice price setting on market mechanisms to establish standard prices in the Banda Aceh market. The data used in this study consist of primary and secondary data, collected through observation, interviews, and documentation. The results show that price setting (tas’ir) in trade and business is permissible if there is a possibility of manipulation leading to price increases. Price setting methods are not prohibited in Islam under the following conditions: the prices set by entrepreneurs or traders should not exploit buyers, meaning they should not take profits above reasonable levels. Price setting should not be coercive towards entrepreneurs or traders as long as they set fair prices and take reasonable profits (not above normal levels). If market equilibrium is disrupted, the government or relevant authorities must intervene in the market while upholding principles of justice for both traders and consumers.